Adopt a neighbourhood: when planners meet schoolchildren - Picone, Marco; Schilleci, Filippo; Lotta, Francesca (AESOP, 2015)
Throughout this paper we will present a project that revolves around the idea of the neighbourhood as an ‘identity container’ and aims at bridging the gap between traditional planning programmes and the new challenges linked both to the crisis of public spaces and to participatory planning. During the last two years, our University has been working in cooperation with the Municipality of Palermo and many primary and secondary schools of the city on a project called ‘La scuola adotta il quartiere’ (‘Schools Adopt Neighbourhoods’). Within the project, planning students from the University guided the schoolchildren (8- to 13-years old) to the discovery of their neighbourhood and its community. Planners also had a key role in helping their younger ‘colleagues’ in the proposal and development of collectively discussed renewal policies: for instance, some of them proposed an urban renewal intervention in the well-known and deprived ZEN neighbourhood, and this proposal was later approved by the Municipality. This process caused a mutual beneficial effect: on the one hand, schoolchildren became more conscious of the idea and nature of their neighbourhood and of the notion of ethical participation. On the other hand, planning students began to concretely explore the social role they are called to play in our contemporary society, and the ethical dilemmas that every participatory project involves.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015